Comparison of two nicotine dependence measures for use with Korean American Women: The FTND and AUTOS - Sun S. Kim (JMIR Publications, 2017)
This study compares psychometric properties of the Fagerström Test for Nicotine Dependence (FTND) and Autonomy over Tobacco Scale (AUTOS), which are measures of nicotine dependence. This study is a secondary analysis of data obtained from a smoking cessation study conducted with 49 Korean American women. We compared the FTND and AUTOS assessed at baseline regarding their internal consistency reliability and concurrent and predictive validities. The AUTOS outperformed the FTND in reliability and concurrent validity by yielding a higher Cronbach's alpha and having significant relationships with smoking-related variables such as age at smoking onset, perceived risks of quitting, and self-efficacy in quitting. In contrast, there was no relationship between the FTND and any of the variables. Both measures had a significant relationship with post-quit nicotine withdrawal symptoms but failed to predict abstinence at follow-ups. The AUTOS seems to be a better assessment tool for Korean American women than the FTND. Before fully adopting the AUTOS as a measure of nicotine dependence for this group, factor structure of the scale should be tested with a larger sample of Korean American women.